Partecipazione creativa dei lavoratori nella 'fabbrica intelligente' Atti del Seminario di Roma, 13 ottobre 2017 - Cipriani, Alberto (Studi e saggi, 2018)
How will work be configured in the future? What new entities and values will emerge following the transformations of the Fourth Industrial Revolution? How decisive will worker participation be for the success of organizations? This book offers concrete experiences of 'creative' participation of workers and managers in companies committed to developing an intelligent organization. The first part of the book offers the contribution of workers, employees or managers who may also have negotiating roles in union bargaining, but who are above all committed to making everything work, offering opportunities that are able to regenerate processes and enhance workers. The second part contains reflections and proposals on how participation experiences can urge the academic world, trade unions, politics and the legislative system to deepen and take into account the new needs of work, in order to build a virtuous circle that supports companies and workers, management and participation in the complex challenges posed by innovation and the competitive world of production.